The Effectiveness of Virtual Laboratory Media in Physics Education: A Meta-Analysis on Students’ Conceptual Understanding and Higher-Order Thinking Skills - Intan Fitriah; Sari Fitra Zawanis (Yayasan Darussalam Bengkulu, 2024)
The rapid development of information and communication technology has reshaped science education, offering innovative solutions to overcome the limitations of traditional laboratories. In physics, where abstract concepts are often difficult to observe directly, virtual laboratories provide safe, cost-effective, and interactive alternatives for experimentation. This study employed a qualitative meta-analysis supported by descriptive quantitative analysis to synthesize evidence from studies published between 2018 and 2022 on the use of virtual laboratories in inquiry-based physics learning. Data were categorized into achievement indicators such as conceptual mastery, critical thinking, problem-solving, and misconception reduction, and analyzed using descriptive statistics and thematic synthesis. The results indicated a substantial improvement in student performance, with mean scores increasing from 66.42 before intervention to 80.35 afterward, alongside a reduction in achievement gaps across ability levels. Conceptual mastery (25%) and conceptual understanding (20%) were the most frequent outcomes, while higher-order thinking indicators collectively represented 30%. Optics and electricity were the most frequently supported topics, reflecting the strength of simulations in visualizing abstract phenomena. The findings confirm that combining inquiry pedagogy with virtual laboratories yields stronger learning outcomes than either approach alone. This study implies that virtual laboratories can democratize access to experimental learning while fostering essential 21st-century competencies in resource-limited educational contexts.